Research in African Literatures (JSTOR)
Research in African Literatures, founded in 1970, is the premier journal of African literary studies worldwide and provides a forum in English for research on the oral and written literatures of Africa. In addition to thought-provoking essays, reviews of current scholarly books appear in every issue, often presented as critical essays, and a forum offers readers the opportunity to respond to issues raised in articles and book reviews. Thematic clusters of articles and frequent special issues reveal the broad interests of its readership.
Keywords: African Studies